Economics literacy among university students: a case study of International Islamic University Malaysia (IIUM) - Hashim, Che Noraini; Kazeem, Bakare (IDOSI Publication, 2013)
The rapid economic growth has necessitated the need for pupils to have an insight in basic daily economics knowledge that are sufficient for practical application. This work is undertaken to ascertain the level of economics literacy among university students. The study firstly measures the levels of awareness of economics literacy and secondly compares the mean scores of economics literacy among students who studied economics and related courses with those who had not. The study also compares the levels of economics literacy among Malaysian students versus the international students. A quantitative research method was adopted and the Test of Economics Literacy (TEL) was used as a research instrument. Undergraduate students from different faculties at the in International Islamic university Malaysia (IIUM) who registered at semester two were the target population. A sample of 200 students consisting of students from economics department and from other course specializations were randomly selected. In the end, only 161 students had set for the Test with almost 60 percent of them were students from the economics faculty, while close to 63 percent of the sample who set for the test comprised of Malaysians. Three hypotheses were tested. It was found that the mean score among respondents in the TEL test with respect to gender, academic background and nationality was 12pts or equivalent to 60 percent; this level of TEL mean score revealed that undergraduates at the IIUM were lacking in the overall economics literacy. Mean score among students who studied economics was found to be relatively higher than those without economics background, but the difference is not statistically significance. Base on the result from the third hypothesis test, it suggests that there exists a significant difference in the mean score of economics literacy between the local and the international second semester's undergraduates at the IIUM. The overall findings, point to the conclusion that about one third of the second semester's undergraduates lacked of economics knowledge and that the exposure to the economics course had positive effect on the TEL mean score. Findings also indicate the consequence of the lack of emphasis on economics education at the Malaysian high school level. © IDOSI Publications, 2013.